2021
DOI: 10.1002/mgg3.1480
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA‐H19 gene plays a significant role in regulating glioma cell function

Abstract: Glioma is the most common type of primary intracranial tumors and is highly lethal due to its pathogenetic location, high invasiveness, and poor prognosis (Gu et al., 2015). According to WHO classification, glioma can be divided into I, II, III, and IV grade levels, and malignancy degree increases with grade. Glioblastoma, classified as Class IV according to its biological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…These findings were consistent with the results of Gao’s 47 on the induction of G1/S arrest in AGS cells upon H. pylori infection. H19 knockdown cells showed an increase in S phase and G2, consistent with the observations made by Ping Liu et al 48 in their study on glioma cells after knockdown of H19. Further analysis showed that H19 knockdown alleviated GZ7/cagA infection-induced S phase arrest and facilitated cell entry into the G2 phase, thereby improving cell cycle progression.…”
Section: Discussionsupporting
confidence: 91%
“…These findings were consistent with the results of Gao’s 47 on the induction of G1/S arrest in AGS cells upon H. pylori infection. H19 knockdown cells showed an increase in S phase and G2, consistent with the observations made by Ping Liu et al 48 in their study on glioma cells after knockdown of H19. Further analysis showed that H19 knockdown alleviated GZ7/cagA infection-induced S phase arrest and facilitated cell entry into the G2 phase, thereby improving cell cycle progression.…”
Section: Discussionsupporting
confidence: 91%
“…lncRNA RP11-390F4.3 is induced by hypoxia/HIF-1 α and is essential for hypoxia-induced EMT and metastasis by activating multiple EMT regulators [ 33 ]. Suppressing the expression of lncRNA-H19 can reduce the invasive behavior of glioma cells [ 34 ]. GAS8-AS1 overexpression inhibits GBM cell proliferation and invasion by downregulating NEAT1 and achieves the purpose of inhibiting the proliferation of glioblastoma cells [ 35 ].…”
Section: Discussionmentioning
confidence: 99%